Evolving Strategies in Peritoneal Dialysis - Zawada, Edward T. (IntechOpen, 2018)
Evolving Strategies in Peritoneal Dialysis is intended as a concise compilation of articles designed to understand the basics of the current practice of the most cost-effective form of life support for patients with end-stage renal disease who require dialysis. Current strategies are understood best with a review of the historical development of catheter materials, solution packaging, and simplified machinery, which allow safe and effective nocturnal treatments. Quantitation of the efficacy of peritoneal dialysis is also reviewed because such calculations were also developed by the pioneers of nephrology to ensure adequacy of dialysis and daily fluid balance, which are responsible for the best chance for long-term patient survival. Comparison of methods for catheter placement is presented as well as the role that a dialysis center plays in the health and success of this form of end-stage renal disease patient care. The novel concept of assisted peritoneal dialysis for the infirm or institutionalized patients is probably the next direction needed to make available this treatment to many more patients than are currently eligible to receive it. This concept is explored in a separate chapter. Finally, professional dialysis staff must monthly assess individuals' nutritional status, bone health, and infection prevention and treatment to ensure the greatest functional status for these patients. This book concludes with a review of each of these topics to expand the mandatory monthly surveillance performed by dialysis centers for each patient who receives home peritoneal dialysis therapy.